2022
DOI: 10.29303/jppipa.v8i4.1797
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Practicality of Student Worksheets on Waves and Sounds for Junior High School Students

Abstract: Student worksheets are one sort of educational material intended to aid students' learning, explore experiences and ideas, and develop students' cognitive, psychomotor, and affective components. As a result, a study of the validity and applicability of the Student Worksheet on waves and sound content for junior high school students was done. The goal of this study was to see if the Student Worksheet was reliable and practical. The research design used in this study is a developmental study. A walkthrough and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…According to research conducted by Cynthia et al (2023), it was found that the product developed had a practitioner assessment percentage of < 80%, so the emodule was included in the practical category and also met the eligibility criteria (valid) so that e-module teaching materials are important. The learning process used e-module also can make student has the critical thinking ability (Azmi et al, 2021;Azmi et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…According to research conducted by Cynthia et al (2023), it was found that the product developed had a practitioner assessment percentage of < 80%, so the emodule was included in the practical category and also met the eligibility criteria (valid) so that e-module teaching materials are important. The learning process used e-module also can make student has the critical thinking ability (Azmi et al, 2021;Azmi et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The descriptive methodology utilized in this study's design has as its primary goal describing the phenomena or condition as it actually exists, unaltered (Azmi et al, 2021). According to Creswell (2010), a descriptive technique is a sort of case study that concentrates on one instance by excluding or limiting other examples.…”
Section: Methodsmentioning
confidence: 99%
“…Based on quantitative data gathered from tests administered to students at SMP Negeri 6 Palembang, it is determined that students' critical thinking abilities are often below average. Some students even receive a score of 0 for the test question items (Azmi et al, 2021;Hikmah et al, 2023;Marlina et al, 2021) have identified five indicators of critical thinking skills, namely the ability to provide simple explanations, build basic skills, inference skills, skills to provide further explanations, as well as skills to organize strategies and tactics. The outcomes of gathering quantitative data are consistent with those obtained from gathering qualitative data, namely through interviews with physics teacher.…”
Section: Figure 2 Graph Of the Average Value Of Each Indicator's Crit...mentioning
confidence: 99%
“…Moreover, this research also involves the participation of agents as respondents to the service survey application on the level of agent satisfaction while sailing. Practical tests on Android survey applications can involve several aspects, including usage time, simplicity of use, and user satisfaction (Azmi et al, 2022;Jumaroh et al, 2023). The level of user satisfaction can be measured using a rating scale or questionnaire ranging from strongly agree to disagree strongly, and a simple formula for calculating the average is Efficiency = results or data obtained/with the previous method results or data obtained with the new application ×100% (Hakiki et al, 2022).…”
Section: Data Analysis Techniquementioning
confidence: 99%